Optimal Public Investment in Economic Centers and the Periphery - Martin Meurers; Johannes Moenius (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We analyze productivity enhancing public expenditure in a spatial economic model with labor mobility, firm-specific increasing returns to scale, and transport costs. Building on Krugman (1991), Fujita, Krugman and Venables (1999) and Redding (2016), we compare optimal investment and tax policies of fiscally autonomous regions to those of a benevolent central planer. We find transport costs and the size of scale effects to influence optimal tax and spending rates under both regimes. For sufficiently low transport costs and low substitutability between manufactured goods, regional fiscal autonomy leads to underinvestment: The lower the transport costs, the lower the local investment, and the higher the potential welfare gain through centralized policies. Our results challenge the view that local public goods should be financed entirely by local governments. They also help explain the recent decline of public investment at the municipal level in fiscally decentralized countries like Germany.
Keywords: R12; R53; H72; H77; 330; quantitative spatial economics; public investment; fiscal federalism